RASA YANG DULU PERNAH ADA: PENGARUH NOSTALGIA PERSONAL DAN HISTORIS TERHADAP KEINGINAN MEMBELI ESKRIM VIENNETTA - Muhammad Fariz; Rahmat Eka Putra (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2020)
This research aims to test the influence of personal nostalgia and historical nostalgia to purchase intention, also to compare between those nostalgia. Using Social Identity Theory (SIT) as a main theory, this research argue that certain cue in advertising may evoke nostalgia in consumer and then acknowledge that the product is related to respondents’ social identity as well as self identity, resulting in positive consumer behavior. We use regression and R2 test to test the hypotheses. The results, which respondents are mainly  millennials, show that both nostalgia affect purchase intention, and interestingly, historical nostalgia has higher influence.